Influencer Marketing and Traditional Marketing in Indonesia - Ester Monica Thamrin; Galuh Septi Utami (Universitas Multimedia Nusantara, 2023)
With the development of technology, marketers from various industries are required to keep abreast of these developments by consistently producing innovations and strategies in marketing their products. One strategy that is currently being intensively used is to use of digital marketing technology to complement current conventional marketing techniques. When it comes to making a purchase, today's buyers are influenced by both personal preferences and societal conformity standards. Influencer marketing is becoming more and more important as efforts are made to implement marketing tactics in the digital world at a time when the use of social media is growing quickly. The aim of this study is to examine and analyzes related marketing activities in Indonesia and how influencer marketing in the leisure food industry influences purchase intentions with interactivity, celebrity expertise, and cross-platform collaboration as factors influencing consumer decisions. The survey method was employed in this study as a quantitative approach. The research is carried out by administering an online questionnaire consisting of 100 consumers divided by males and females of different ages online as the consumer sample about the behavior habits of food consumers on the Internet. The study focus on questions that are tailored to the 3 hypotheses such as influencer marketing interactivity affects purchase intention, influencer marketing celebrity worship affects purchase intention, and influencer marketing cross-channel cooperation affects purchase intention. The result of this study is study's findings support the notion that consumer purchases in the recreational food sector are positively correlated with the study's findings.